4(y-4)=-9y+49

Simple and best practice solution for 4(y-4)=-9y+49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(y-4)=-9y+49 equation:


Simplifying
4(y + -4) = -9y + 49

Reorder the terms:
4(-4 + y) = -9y + 49
(-4 * 4 + y * 4) = -9y + 49
(-16 + 4y) = -9y + 49

Reorder the terms:
-16 + 4y = 49 + -9y

Solving
-16 + 4y = 49 + -9y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '9y' to each side of the equation.
-16 + 4y + 9y = 49 + -9y + 9y

Combine like terms: 4y + 9y = 13y
-16 + 13y = 49 + -9y + 9y

Combine like terms: -9y + 9y = 0
-16 + 13y = 49 + 0
-16 + 13y = 49

Add '16' to each side of the equation.
-16 + 16 + 13y = 49 + 16

Combine like terms: -16 + 16 = 0
0 + 13y = 49 + 16
13y = 49 + 16

Combine like terms: 49 + 16 = 65
13y = 65

Divide each side by '13'.
y = 5

Simplifying
y = 5

See similar equations:

| -10j-10=-70 | | 3sinx-1=2 | | 64=2n-6 | | 8x+15=6x-13 | | 9x-8=56 | | -4w-1=9(w-1) | | 3x-2=23-2x | | 4a-4=8ta | | 9(z-4)=3z | | 8b+10+b-5=23+2b+2-b | | 1436=4*3.14r^2 | | -9(v-7)=2v-36 | | 14(x+30)=210 | | 11m-6m-9= | | Y^2+2CX=C^2 | | -5(2y+7)+8y=3(y-1)+2y | | 6a+-11=13 | | 24+6n=6 | | y=-5t^2+20t+.8 | | 93=2x+5+3x-2+3x+x | | B+5=2b+12 | | y=C^2+C^2 | | 3X^6=8 | | -2p+-4=2 | | 7x^2-33x-20=0 | | 6.7(x-2)=0.3x+42.6 | | 5b+10=2b+31 | | 4x-6y=-1 | | 2x?x/2+x+1/4=6x | | G(y)=2x+5 | | 0=4x-6y | | y=100(3x) |

Equations solver categories